WEIGHT REBOUND POST GLP-1 RA CESSATION: THE IMPORTANCE OF GRADUAL TAPERING AND PATIENT EDUCATION - MA, Nurafiza; Ng, Ooi Chuan; Susinadan, Jolyn Rumefla (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have demonstrated significant efficacy in weight management. However, abrupt discontinuation often leads to an uncontrollable appetite rebound and subsequent weight regain. This phenomenon underscores the need for structured tapering protocols and comprehensive patient education to ensure sustainable weight management post-therapy cessation. CASE A 54-year-old female with obesity (BMI 33.8) was initiated on subcutaneous Saxenda (liraglutide) for weight management. She successfully escalated to a 3 mg daily dose, tolerating mild gastrointestinal side effects. Despite an initial weight reduction (94.5 kg >92.4 kg), she discontinued treatment due to injection site reactions. Three months post-discontinuation, her weight increased to 96.7 kg (BMI 35.95) with increased appetite and dietary non-compliance. Upon restarting therapy, a gradual dose escalation was advised to minimize adverse effects and improve adherence. The patient also received structured education on medication tapering, dietary modifications, and lifestyle interventions. CONCLUSION This case highlights the challenges of abrupt GLP-1 RA discontinuation and the subsequent weight rebound. A strategic tapering plan is essential to mitigate appetite dysregulation and sustain weight loss. Moreover, patient education on the physiological impact of cessation, proper injection techniques, and behavioral strategies is crucial in optimizing long-term obesity management outcomes. Health practitioners must emphasize these aspects to ensure adherence and enhance treatment success.